Komparasi Biaya Panen Padi Sawah Antara Petani Mengadopsi dan Tidak Mengadopsi Teknologi Harvester Combine Machine di Desa Padang Siring Kecamatan Seginim Kabupaten Bengkulu Selatan - Muhammad Yusun; Herri Fariadi; Evi Andriani (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2024)
This research aims to analyze the comparison of lowland rice harvest costs between traditional methods and the use of combine harvester technology in Padang Siring Village, Seginim District, South Bengkulu Regency. A total of 56 farmers were research respondents, consisting of 28 farmers using combine harvesters and 28 farmers using traditional methods. Primary data was collected through observation and interviews, while secondary data came from related agency documents. The research results show that the average cost of harvesting using traditional methods reaches IDR 2,560,000, while the cost of harvesting using a Combine Harvester is IDR 1,865,000, with a cost difference of IDR 695,000. Combine Harvester provides higher cost efficiency because it only requires IDR 500/kg for production wages and harvest time is shorter, namely one day for one hectare. In contrast, traditional methods require more labor and time, so they are more expensive. Reasons why farmers choose traditional methods include muddy land conditions, narrow rice fields, and inconsistent harvests. This research concludes that the use of a Combine Harvester is more efficient in terms of cost and time, but its implementation is still hampered by land conditions. It is hoped that this study can become a reference in encouraging the adoption of appropriate technology in the agricultural sector to support sustainable food self-sufficiency.